Active tectonics and earthquake potential of the Myanmar region. Issue 4 (25th April 2014) - Wang, Yu; Sieh, Kerry; Tun, Soe Thura; Lai, Kuang‐Yin; Myint, Than
Abstract: This paper describes geomorphologic evidence for the principal neotectonic features of Myanmar and its immediate surroundings. We combine this evidence with published structural, geodetic, and seismic data to present an overview of the active tectonic architecture of the region and its seismic potential. Three tectonic systems accommodate oblique collision of the Indian plate with Southeast Asia and extrusion of Asian territory around the eastern syntaxis of the Himalayan mountain range. Subduction and collision associated with the Sunda megathrust beneath and within the Indoburman range and Naga Hills accommodate most of the shortening across the transpressional plate boundary. The Sagaing fault system is the predominant locus of dextral motion associated with the northward translation of India. Left‐lateral faults of the northern Shan Plateau, northern Laos, Thailand, and southern China facilitate extrusion of rocks around the eastern syntaxis of the Himalaya. All of these systems have produced major earthquakes within recorded history and continue to present major seismic hazards in the region. Key Points: We provide an up‐to‐date active fault map for Myanmar and its surroundings We summarize historical seismic activity and its plausible sources We discuss the earthquake potential of the region